ANALISIS USABILITY PADA APLIKASI SISTEM PELAYANAN RAKYAT SID`OARJO (SIPRAJA) MENGGUNAKAN METODE HEURISTIC EVALUATION DAN SYSTEM USABILITY SCALE - firzatullah, arsa (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
This study aims to analyze the usability of the Sidoarjo Public Service System (SIPRAJA) application using Heuristic Evaluation and the System Usability Scale (SUS) methods. The SUS results provide an average score of 49.63. The Heuristic Evaluation identifies problems and strengths based on design principles, while SUS quantitatively assesses the application's usability. The Heuristic Evaluation results show that most usability aspects fall into the